An Investigation of Mental Toughness, Anxiety, and Self-Talk in Pencak Silat Athletes in Tangerang Regency, Indonesia - Eni Sumiyati; Aridhotul Haqiyah; Dani Nur Riyadi; Hanifah Aulia Rahmah (Universitas Negeri Semarang, 2026)
Psychological factors are essential in supporting athletic performance, particularly in combat sports such as pencak silat, which involve high competitive pressure. This study aimed to examine mental toughness, anxiety, and self-talk among pencak silat athletes in Tangerang Regency, Indonesia and to analyze their relationship based on gender and competition level. The participants consisted of 31 male and female athletes preparing for the Regional Sports Week (PORPROV), selected through purposive sampling. Data were collected using standardized questionnaires measuring mental toughness, competitive anxiety, and self-talk. The data were analyzed using descriptive statistics, cross-tabulation, and correlation analysis with SPSS version 26.0. The results showed that male athletes, predominantly aged 17–23 years, demonstrated higher mental toughness and lower anxiety levels compared to female athletes, particularly at national and provincial competition levels. Athletes competing at higher levels tended to exhibit stronger mental toughness and more frequent self-talk, while also experiencing increased anxiety due to greater performance demands. Overall, the findings indicate a close interaction between mental toughness, anxiety, and self-talk, highlighting the importance of psychological skill development to enhance mental readiness and competitive performance among pencak silat athletes.